1992
DOI: 10.1095/biolreprod47.4.656
|View full text |Cite
|
Sign up to set email alerts
|

Leydig Cells Express Neural Cell Adhesion Molecules in Vivo and in Vitro1

Abstract: 1bc neural cdI adbcsioo molccule (NCAM) polypepddes are aprascd by numerous tisIues durina embryool.c devdopment, wberc tbey are InvolYed In cdI
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 38 publications
3
17
0
1
Order By: Relevance
“…However, since the immunostaining was not restricted to synaptic areas of the receptor cells, other authors postulate that it cannot be argued that NCAM participates in synaptic formation [39]. NCAM has also been described in multiple endocrine and neuroendocrine cells including pituitary cells, adrenal cells, pancreatic islet cells, thyroid C cells, testicular Leydig cells, ovarian granulosa cells and pulmonary neuroendocrine cells [5,12,17,19,20,21,23,24,28,30,33,37]. Since most of these cells lack contacts with nerve fibres, NCAM cannot obviously act in nerve-cell recognition in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the immunostaining was not restricted to synaptic areas of the receptor cells, other authors postulate that it cannot be argued that NCAM participates in synaptic formation [39]. NCAM has also been described in multiple endocrine and neuroendocrine cells including pituitary cells, adrenal cells, pancreatic islet cells, thyroid C cells, testicular Leydig cells, ovarian granulosa cells and pulmonary neuroendocrine cells [5,12,17,19,20,21,23,24,28,30,33,37]. Since most of these cells lack contacts with nerve fibres, NCAM cannot obviously act in nerve-cell recognition in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Such contribution of the endothelium is presumably in series and complements the epithelial component(s) of the BTB that is formed by the tight junctions among Sertoli cells. (50,51), suggesting that they, like astrocytes, are of ectodermal origin. Previously, S-100, a marker of astrocytes (25), was demonstrated in Leydig cells (52).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data of all these studies, NCAM-140 could be involved in cell-to-cell adhesion (granulosa cells in the growing follicle), as well as cell separation (antrum formation). In most previous studies NCAM has been suggested to play a role in the autoadhesion of NCAMbearing cells of the same kind via a homophilic binding, such as in the endocrine cells of the pancreatic islet, in the adenohypophysis, in adrenal cortex, adrenal medulla and in the testis [10,15]. In these cases the 'recognition site' of NCAMs, which was identified as lying within the third Ig domain [8], may be modulated by alternative splicing of the neighbouring fourth Ig domain.…”
Section: Discussionmentioning
confidence: 99%
“…NCAMs were first found in the nervous system, but subsequently were also found in polypeptide hormoneand steroid-producing endocrine cells [10][11][12][13][14][15]. NCAMs allow the formation of cell clusters by auto-adhesion of neighboring NCAM-bearing cells.…”
Section: Introductionmentioning
confidence: 99%